Roles of calcium signaling in cancer metastasis to bone - Tianying Xie; Sitong Chen; Jiang Hao; Pengfei Wu; Xuelian Gu; Haifeng Wei; Zhenxi Li; Jianru Xiao (Open Exploration Publishing Inc., 2022)
Bone metastasis is a frequent complication for cancers and an important reason for the mortality in cancer patients. After surviving in bone, cancer cells can cause severe pain, life-threatening hypercalcemia, pathologic fractures, spinal cord compression, and even death. However, the underlying mechanisms of bone metastasis were not clear. The role of calcium (Ca2+) in cancer cell proliferation, migration, and invasion has been well established. Interestingly, emerging evidence indicates that Ca2+ signaling played a key role in bone metastasis, for it not only promotes cancer progression but also mediates osteoclasts and osteoblasts differentiation. Therefore, Ca2+ signaling has emerged as a novel therapeutical target for cancer bone metastasis treatments. Here, the role of Ca2+ channels and Ca2+-binding proteins including calmodulin and Ca2+-sensing receptor in bone metastasis, and the perspective of anti-cancer bone metastasis therapeutics via targeting the Ca2+ signaling pathway are summarized.